The Covid-19’s Effect on Increasing Domestic Violence During Quarantines - Salih, Hazha Mohammed Salih (Sulaimani Journal for Humanities, 2026)
Domestic Violence or violence against one's partner, or domestic abuse, refers to a pattern of abusive behaviour in a relationship in which one person attempts to control or dominate the other. A variety of forms of abuse can be manifested, such as physical violence, emotional abuse, psychological abuse, sexual abuse, financial control, isolation from friends and family, or intimidation and threats. There is a possibility of domestic violence occurring in any type of intimate relationship, regardless of gender, age, or socioeconomic status. The physical and psychological effects of domestic violence can be severe. In this study the main question is: Has domestic violence been increased during quarantines as a result of the Covid-19? As people were stuck and isolated at home also their freedom was taken away from them, these reasons can lead people to change their behaviour towards their partner, children, family or any other members who live together. In this study, the researcher tries to find out to what extent COVID-19 has affected on increasing domestic violence? Furthermore, for previous studies, two researches were used worldwide for obtaining information about domestic violence. As well as with connecting to Kurdish society the researcher has interviewed director of women’s shelter in Erbil and deputy general manager Combating Violence Against Women and Family (CVAWF) in KRG. Moreover, for methodology, semi- structured interview was used to interview five females and five males in Kurdistan for gathering information. Overall, all interviewees and director of women’s shelter in Erbil believed that COVID-19 has brought families closer to each other. On the other hand, deputy general manager of CVAWF had different point of view based on survey he carried out that the rate for domestic violence has been increased especially in Iraq.
Keywords: Domestic Violence; COVID19; Quarantine; patriarchal; social phenomenon